SOP3: a web-based tool for selection of oligonucleotide primers for single nucleotide polymorphism analysis by Pyrosequencing®. (January 2005) - Alexander, Angela M.; Pecoraro, Christopher; Styche, Alexis; Rudert, William A.; Benos, Panayiotis V.; Ringquist, Steven; Trucco, Massimo
SOP 3 is a web-based software tool for designing oligonucleotide primers for use in the analysis of single nucleotide polymorphisms (SNPs). Accessible via the Internet, the application is optimized for developing the PCR and sequencing primers that are necessary for Pyrosequencing®. The application accepts as input gene name, SNP reference sequence number, or chromosomal nucleotide location. Output can be parsed by gene name, SNP reference number, heterozygosity value, location, chromosome, or function. The location of an individual polymorphism, such as an intron, exon, or 5′ or 3′ untranslated region is indicated, as are whether nucleotide changes in an exon are associated with a change in an amino acid sequence. SOP 3 presents for each entry a set of forward and biotinylated reverse PCR primers as well as a sequencing primer for use during the analysis of SNPs by Pyrosequencing. Theoretical pyrograms for each allele are calculated and presented graphically. The method has been tested in the development of Pyrosequencing assays for determining SNPs and for deletion/insertion polymorphisms in the human genome. Of the SOP 3 -designed primer sets that were tested, a large majority of the primer sets have successfully produced PCR products and Pyrosequencing data.